Expressive Therapies for Sexual Issues A Social Work Perspective - Loue, Sana.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Sexuality is a central part of our identity as humans, but when individuals struggle with matters of sexual identity, orientation, or expression, these issues can be embarrassing for clients to discuss$1 (Band equally hard for practitioners to feel comfortable with. Expressive Therapies for Sexual Issues challenges social work practitioners to think outside conventional forms of treatment as well as conventional ideas about sexuality. Reflecting the diversity of sexual experience (both positive and negative), this concise clinical guide introduces readers to a range of art-based therapies suited to working with clients on their intimate concerns and helping give voice to concepts and feelings that are often difficult to name. Case examples depict a gamut of clients$1 (Ba group as diverse as gender-questioning youth, abuse survivors, and sex offenders$1 (Bas they strive for greater self-awareness, negotiate the sexual in their lives, and move beyond trauma, detailing practitioners$1 (Bcreative interventions as companions on these journeys. Contributors keep a clear focus on the delicacy of the therapeutic relationship, ethical fine lines, and the ongoing need for sensitivity and open-mindedness as they examine healing possibilities for: Music Photography Poetry Monologue and performance Visual art Movement and dance. Sandplay Reader-friendly and jargon-free, Expressive Therapies for Sexual Issues breaks consequential new ground for social work professionals and counselors seeking to integrate expressive modalities, and more familiarity with sexual matters, into their practice.s
Keywords: Social sciences; Psychotherapy; Social work; Applied psychology; Social Sciences; Social Work; Psychotherapy and Counseling; Psychotherapy